Network Analysis of Y-STR in Six Ethnic Populations in Guangxi and Its Forensic Significances - Xiao, Y; Deng, P; Chang, K C; Ma, Q; Qian, E F; Yu, J H; Cheng, B W; Li, C X; Jiang, L (Fa yi xue za zhi, 2019)
Objective To explore the distribution of genetic structure of Y-SNP and Y-STR genetic markers in different ethnic groups and its application in forensic science. Methods SNaPshot minisequencing was used to detect the polymorphisms of 12 Y-SNP loci in 439 males from 6 ethnic groups, including Guangxi Han, Guangxi Jing, Guangxi Miao, Guangxi Yao, Guangxi Zhuang and Guangxi Dong. DNATyperTM Y26 kit was used to multiplex-amplify 26 Y-STR loci. The PCR products were analyzed by 3130xl genetic analyzer. The network analysis of Y-STR haplotype under the same Y-SNP haplogroup was analyzed by Network 5.0 software. Results Six haplogroups defined by 12 Y-SNP loci were detected in 6 ethnic groups, and 362 haplotypes were detected in 26 Y-STR loci. The haplotype diversity was 0.996 6. In the C haplogroup, the samples from Guangxi Yao, Guangxi Zhuang and Guangxi Dong were clustered on different branches; in the O1 haplogroup, those from Guangxi Zhuang, Guangxi Miao and Guangxi Jing were relatively independent and clustered separately; in the O2 haplogroup, some samples from Guangxi Miao and Guangxi Yao were gathered in a cluster. Conclusion Based on the Y-STR network analysis of samples with identical haplogroup of Y-SNP, some ethnic groups can be preliminarily distinguished, which could be used to infer male suspects' ethnic group through detecting their genetic markers left in the crime scene.